Belarus : Window of Opportunity to Enhance Competitiveness and Sustain Economic Growth, A Country Economic Memorandum (CEM) for the Republic of Belarus, Volume 2, Executive Summary - World Bank (Washington, DC, 2012)
This Country Economic Memorandum (CEM) for the Republic of Belarus takes stock of the growth trends in the country's economy since 1996, reviews the evidence of the accumulated challenges and risks within the existing growth patterns, and provides recommendations aimed at strengthening growth sustainability. In sum, while economic growth in the last nine years has been impressive, the report argues that maintaining the current growth strategy would lead to a gradual erosion of economic competitiveness. The government should make significant policy adjustments by reorienting its policies toward ensuring a better business environment, and a smaller sized government. Current international and domestic environment are favorable for supporting a policy shift toward the acceleration of structural reforms. At the moment, the government is well equipped to mitigate the potential costs of these reforms, because the policy settings are largely determined by the growing economy, the positive trends in both the enterprise and the household sectors, favorable developments in the global economy, low debt, and the strong administrative capacity of the state. This situation could change: various pressures might become stronger, and then these same reforms would become politically more costly, and fiscally more risky. In short, the current window of opportunity should be used to ensure that the authorities' growth and poverty objectives are sustainable in the medium to long terms. The analysis in this report has documented a significant and broad-based growth, while pointing to the erosion of several important factors that have driven this growth recently. The Belarusian economy is facing a considerable risk of declining competitiveness. To sustain growth, a significant policy adjustment is necessary to enhance market discipline, and encourage new business entry.